State of Agriculture in Sverdlovsk Region during Implementation of Radical Socio-Economic Reforms (1985-2000) - V. N. Mamyachenkov (Научный диалог, 2017)
The article is devoted to the subject insufficiently developed in the national historiography, especially in regard to its regional dimension. The study is conducted on materials of the Centre of documentation of public organizations of Sverdlovsk region with the assistance of the scientific and publicistic literature. The relevance of the topic is determined by its high importance for the social sciences, especially history. Scientific novelty of the work is seen in the fact that the new materials discovered by the author in mentioned archive are introduced into scientific usage. The purpose of the article was to identify the features of the crisis of the 1980s-1990s in the agricultural sector of the Sverdlovsk region. It is noted that the years mentioned in the title of this article were without exaggeration crucial for our state. It is argued that there is a wide range of opinions about the causes and driving forces of the crisis of 1980s-1990s in the USSR and Russia. It is claimed that the process of destruction of the administrative-command system of economic management was accompanied by a significant decrease of all parameters of the latter and the deterioration of living conditions of the general population. It is stated that herewith the agro-industrial complex had to suffer even more than the industrial sector of the economy, being in fact always subsidized. It is declared that the agriculture of the region has withstood the first onslaught of a systemic crisis: main indicators of its activity began to decline irreversibly in the mid 1990-ies. It is emphasized that the problem of the systemic crisis of 1980-1990-ies in Russia is still mainly developed only on the Federal level. It is proved that the crisis in the agrarian sector of economy of Sverdlovsk region had a number of features and, in addition, it cannot be considered accomplished.